2022
DOI: 10.1001/jamasurg.2022.4765
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient Belief About Success of Antibiotics for Appendicitis and Outcomes

Abstract: ImportanceA patient’s belief in the likely success of a treatment may influence outcomes, but this has been understudied in surgical trials.ObjectiveTo examine the association between patients’ baseline beliefs about the likelihood of treatment success with outcomes of antibiotics for appendicitis in the Comparison of Outcomes of Antibiotic Drugs and Appendectomy (CODA) trial.Design, Setting, and ParticipantsThis was a secondary analysis of the CODA randomized clinical trial. Participants from 25 US medical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…First, we note that appendicolith was more common in the unsuccessful/unsure group (34 [37%]) than in the completely successful group (27 [24%]) or intermediate group (54 [25%]) . Another study showed that appendicolith was a risk factor for failure of antibiotics in appendicitis treatment, and this was also confirmed by the CODA randomized clinical trial, which found that appendicolith was associated with a nearly 2-fold increased risk of undergoing appendectomy within 30 days of initiating antibiotics .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…First, we note that appendicolith was more common in the unsuccessful/unsure group (34 [37%]) than in the completely successful group (27 [24%]) or intermediate group (54 [25%]) . Another study showed that appendicolith was a risk factor for failure of antibiotics in appendicitis treatment, and this was also confirmed by the CODA randomized clinical trial, which found that appendicolith was associated with a nearly 2-fold increased risk of undergoing appendectomy within 30 days of initiating antibiotics .…”
mentioning
confidence: 99%
“…In Figure 2 in the article by the Writing Group for the CODA Collaborative, in the 95% CI of risk difference in the completely successful row, the data of upper limits are different from the description in the Results section and seem to be missing minus signs. This is also the case for 95% CIs in the unadjusted risk difference column in Figure 3 in the article.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Reply We appreciate the comments from Yan and Sha regarding our recently published article . At the time the CODA trial was being conducted, the relationship between appendicoliths and appendectomy after antibiotics in adults was not known.…”
mentioning
confidence: 99%
“…Lastly, regarding the question of appendicolith and appendectomy, because of its importance, we adjusted for appendicolith status in our adjusted risk differences (see Figure 2 in our article). We found that differences between the completely successful and unsuccessful/unsure groups are similar before (risk difference, −14.08; 95% CI, −25.46 to −2.70) and after (adjusted risk difference, −13.49; 95% CI, −24.57 to −2.40) adjustment.…”
mentioning
confidence: 99%